An observational multicentre study on the efficacy and safety of assisted reproductive technologies in women with rheumatic diseases. Issue 1 (22nd February 2019) - Reggia, Rossella; Andreoli, Laura; Sebbar, Houssni; Canti, Valentina; Ceccarelli, Fulvia; Favaro, Maria; Hoxha, Ariela; Inversetti, Annalisa; Larosa, Maddalena; Ramoni, Veronique; Caporali, Roberto; Conti, Fabrizio; et al.
Abstract: Objectives: The aim was to determine whether assisted reproductive technologies (ARTs) confer additional risk in rheumatic patients (in terms of disease flare and fetal–maternal complications) and whether, if performed, their efficacy is affected by maternal disease. Methods: Sixty infertile rheumatic women undergoing 111 ART cycles were included. Clinical pregnancy rate, live birth rate, maternal disease flares and maternal–fetal complications were recorded. Results: One hundred and eleven ART cycles in 60 women were analysed. We reported 46 pregnancies (41.4%), 3 (3.1%) cases of ovarian hyperstimulation syndrome and no cases of thrombosis during stimulation, pregnancy and puerperium. One or more maternal complication was reported in 13 (30.2%) pregnancies, and fetal complications occurred in 11 fetuses (21.1%). The live birth rate was 98%, but we reported three (6%) perinatal deaths in the first days of life. During puerperium, we recorded one (2.5%) post-partum haemorrhage and one (2.5%) articular flare. Conclusion: The safety and efficacy of the ARTs, demonstrated in the general population, seems to be confirmed also in rheumatic patients. No evidence was found to advise against their application, and the choice of therapy should be made depending on the patient's risk profile, irrespective of whether the pregnancy is natural or artificial induced.